1990
DOI: 10.1021/ac00217a026
|View full text |Cite
|
Sign up to set email alerts
|

Identification of archaeological and recent wood tar pitches using gas chromatography/mass spectrometry and pattern recognition

Abstract: An analytical method has been developed for the assignment of recent and archaeological wood tar pitches to the species of trees used for their preparation. It Incorporates the prepurlflcatlon by Kugelrohr distillation and solid-phase extraction followed by gas chromatography/mass spectrometry analysis. Distribution patterns of volatile, thermostable triterpenoids and steroids characterizing the biological origin of the pitches are evaluated by principal component analysis (PCA) and discriminant component anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
59
0
6

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(69 citation statements)
references
References 7 publications
3
59
0
6
Order By: Relevance
“…), it is unlikely that the types of wood used by the plants varied greatly since all chemical plants in the current study lay within forests of similar composition typical of the southern reaches of the hemlock-white pine-northern hardwood forests of eastern North America (Nichols 1935). The tree species from which wood tars and pitches were derived could be determined by analysis of patterns of their triterpenoid and steroid composition (Hayek et al 1990). However, wood chemical plants in the Allegheny High Plateau preferentially used maple and beech because of their greater yield of acetic acid and methanol (Taber 1975).…”
Section: Discussionmentioning
confidence: 88%
“…), it is unlikely that the types of wood used by the plants varied greatly since all chemical plants in the current study lay within forests of similar composition typical of the southern reaches of the hemlock-white pine-northern hardwood forests of eastern North America (Nichols 1935). The tree species from which wood tars and pitches were derived could be determined by analysis of patterns of their triterpenoid and steroid composition (Hayek et al 1990). However, wood chemical plants in the Allegheny High Plateau preferentially used maple and beech because of their greater yield of acetic acid and methanol (Taber 1975).…”
Section: Discussionmentioning
confidence: 88%
“…Concerning the instrumental equipment and the temperature profile during the manufacturing process pitch production was done as published previously 22,25 .…”
Section: Pitch Productionmentioning
confidence: 99%
“…Tar from Betulaceae bark has been found on arrowheads and flint tools from the prehistoric age and the tar has been interpreted as a residue of the original adhesives [3][4][5][6][7][8][9][10][11]. A chemical study of amorphous materials recovered from flint artefacts found in Campitello (Arezzo, Italy) revealed that birch bark tar was already being produced in the early-Palaeolithic period, and this represents the oldest finding of birch bark tar known until now [9,12].…”
Section: Introductionmentioning
confidence: 99%